Women’s Perception, Familial and Mass Media Influence upon Ratus Vaginal Douche Usage in Bali, 2013 - Widyastuti; Nazrina Zuryani; I Nyoman Mangku Karmaya (Universitas Udayana, 2014)
Background and purpose: The ratus vaginal douching technique is a treatment by evaporation in the genital area, that compound is called “ratus”. There are a number of controversies surrounding the ratus technique, especially regarding the benefits and detrimental aspects. This study applies a behaviour model Green (2007) with a focus on three factors: the determinant, supporting and stimulant. This study was aimed to understand the relationship perception, socio economic, familial, and mass media upon ratus vaginal douching usage. Methods: This study used a quantitative approach with an analytic observational cross-sectional design. Study used random sampling of 63 samples that taken from 3 different Spas. Results: The respondents were 44 (69.8%) who performed the ratus vaginal douching and 19 (30.2%) who had not performed. Results indicated that the variables of perception, knowledge, familial, and the mass media showed a significant correlation with the value of (p<0.05). The result of multivariate analysis came from mass media that had the greatest influence with OR=8.47 (95%CI: 1.21-59.42). Conclusion: Mass media had the greatest influence on the use of the ratus vaginal douching in Bali Province.